P10.03 ENDOTHELIUM-SPECIFIC CALCIUM-ACTIVATED POTASSIUM CHANNELS: TARGETS FOR ALDOSTERONE - V. Griol-Charhbili; A. Nguyen Dinh Cat; G. Palais; L. Loufrani; D. Henrion; N. Farman; F. Jaisser (Artery Research, 2009)
To define the vascular role of the mineralocorticoid receptor (MR) in cardiovascular pathophysiology, we generated a conditional transgenic mouse model with MR overexpression in the endothelium. We previously described increase sensitivity to several vasoconstrictors in mesenteric arteries such as in aorta of mice over-expressing the MR in the endothelium (MR-EC) in presence of a normal relaxation to vasodilatators. In vivo, blood pressure (BP) was increased in awaked MR-EC mice, as compared to the controls (CT) (tail-cuff method). We have investigated the role of the small (SKCa), and the intermediate (IKCa) and the big (BKCa) conductance potassium channels in vascular function. In infra-renal aorta, endothelial SKCa and IKCa channel blockade (Apamin 1 μM+TRAM-34 1 μM) unmasked an impaired relaxation to acetylcholine in MR-EC mice as compared to controls. Inhibition of the smooth muscle specific BKCa channel with Iberiotoxin (0.1 μM) blunted the higher phenylephrin-induced contractile response observed in MR-EC as compared to CT. These pharmacological data suggest that endothelial MR overexpression is associated with an increased activity of EDHF-mediating endothelial Ca-activated K channels and a functional decrease of the smooth-muscle BKCa channel activity. Western-blot analyses of the protein expression levels of these channel subunits were performed. None of them showed significant modulation, suggesting that channel activity, rather than expression level, is affected in this model. MR activation specifically in endothelial cells is therefore associated with increased BP and altered vascular reactivity, in absence of renal collecting duct mediated MR effects. This may be related to ion channels remodeling.